(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tymofiyeva L. Yе. An innovative strategy of management activity of the modern leader in the conditions of sustainable development of society. The article describes the main principles of modernization of management innovation leader of an educational institution in sustainable development of the society.